Dumbo - Holloway, Sterling; Bing, Herman, 1889-1947.; Felton, Verna; Walt Disney Productions; Buena Vista Home Entertainment (Firm) ([Burbank, CA] : Buena Vista Home Entertainment, 2001)
A baby elephant with oversized ears is ridiculed by all the circus animals and finally befriended by a mouse. Dumbo becomes the world's only flying elephant.
Originally produced as a motion picture in 1941.
Featuring the voices of: Sterling Holloway, Herman Bing, Verna Felton.
MPAA rating: G.
Also issued on DVD.
VHS.
Closed-captioned.
Keywords: Elephants -- Juvenile drama; Feature films; Animated films; Children's films; Video recordings for children; Video recordings for the hearing impaired